[Memo from Karen Doyne to Fred Panzer regarding American Council for Capital Formation conference] - KAREN DOYNE (Tufts Archival Research Center, 2007)
Missing Attachments; Memo from Karen Doyne to Fred Panzer regarding the American Council for Capital Formation Conference. Introduces missing text of Senator Durenbergers remarks at a consumption tax conference. Reports calling BNA. Finds that Durenberger's press operation is "virtually in chaos."